Isoscapes of tree-ring carbon-13 perform like meteorological networks in predicting regional precipitation patterns - del Castillo, Jorge; Aguilera, Monica; Voltas, Jordi; Pedro Ferrio, Juan (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2013)
Stable isotopes in tree rings provide climatic information with annual resolution dating back for centuries or even millennia. However, deriving spatially explicit climate models from isotope networks remains challenging. Here we propose a methodology to model regional precipitation from carbon isotope discrimination (Delta C-13) in tree rings by (1) building regional spatial models of Delta C-13 (isoscapes) and (2) deriving precipitation maps from Delta C-13-isoscapes, taking advantage of the response of Delta C-13 to precipitation in seasonally dry climates. As a case study, we modeled the spatial distribution of mean annual precipitation (MAP) in the northeastern Iberian Peninsula, a region with complex topography and climate (MAP = 303-1086 mm). We compiled wood Delta C-13 data for two Mediterranean species that exhibit complementary responses to seasonal precipitation (Pinus halepensis Mill., N = 38; Quercus ilex L.; N= 44; pooling period: 1975-2008). By combining multiple regression and geostatistical interpolation, we generated one Delta C-13-isoscape for each species. A spatial model of MAP was then built as the sum of two complementary maps of seasonal precipitation, each one derived from the corresponding Delta C-13-isoscape (September-November from Q. ilex; December-August from P. halepensis). Our approach showed a predictive power for MAP (RMSE = 84 mm) nearly identical to that obtained by interpolating data directly from a similarly dense network of meteorological stations (RMSE = 80-83 mm, N= 65), being only outperformed when using a much denser meteorological network (RMSE = 56-57 mm, N = 340). This method offers new avenues for modeling spatial variability of past precipitation, exploiting the large amount of information currently available from tree-ring networks.
CitationCitationThe following values have no corresponding Zotero field: pub-location: 2000 FLORIDA AVE NW, WASHINGTON, DC 20009 USA publisher: AMER GEOPHYSICAL UNION
Keywords: ARCHAEOBOTANICAL REMAINS; ATMOSPHERIC CO2; CARBON-ISOTOPE DISCRIMINATION; climate; DELTA-C-13; PINUS-HALEPENSIS; RAINFALL; STABLE-ISOTOPES; Temperature

The role of interannual rainfall variability on runoff generation in a small dry sub-humid watershed with disperse tree cover - Schnabel, S; Gomez GUTIÉRREZ, A (Cuadernos de Investigación Geográfica, 2013)
Recent studies in small experimental catchments under Mediterranean-type climate revealed a complex hydrological catchment response, presenting saturation excess runoff generation and, to a minor degree, infiltration excess flow. Many of these catchments, however, belong to areas with sub-humid or humid Mediterranean climate. Catchment studies were carried out since 1991 in savannah-like grazed land (dehesas), which are widespread in south-western Spain, and also elsewhere in the Mediterranean. Albeit knowledge gained by previous studies, no thorough analysis has been carried out on the temporal variation of discharge production using the complete dataset. The objectives include i) an analysis of the temporal variation of discharge and rainfall at different temporal scales, ii) exploration of the role of antecedent soil moisture conditions in runoff production, iii) empirical modeling of rainfall- runoff relationships at the event scale and iv) definition of the importance of interannual rainfall variation on discharge production. The analysis were based on rainfall and runoff which were monitored at a time resolution of 5 minutes and periodically measured soil moisture from various depth in the valley bottom. Regression analysis as well as the comparison of hydrographs illustrate on the importance of antecedent rainfall conditions. Soil moisture in the valley bottom was crucial to understand the hydrological behaviour of the catchment. A soil moisture threshold of 0.37 m3 m-3 was defined above which runoff coefficients increase sharply. This situation is reached with 170 mm of antecedent rain falling in a continuous way. The results indicate that saturation excess flow and preferential subsurface flow processes are responsible of most of the runoff generated. Hortonian type overland flow dominates under dry soil conditions and is produced by high intensity rainfall. Non-linear regression analysis with data grouped according to antecedent catchment conditions produced highly significant regression models, explaining event discharge with three variables: Maximum 60-minute rainfall intensity (I60), event rainfall minus I60 and mean antecedent daily rainfall. Variability of monthly runoff is best explained by interannual rainfall variation rather than by mean seasonal distribution. During droughts, which are a common feature in the Mediterranean, discharge was very low. Runoff is highly concentrated in time with 10% of the months accounting for 85% of total discharge.
Keywords: Dehesa; discharge; Drought; empirical modelling; RAINFALL; Soil moisture

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.

Leaf fluctuating asymmetry of Holm oak in response to drought under contrasting climatic conditions - Hódar, José a. (Journal of Arid Environments, 2002)
Fluctuating asymmetry (FA) can be defined as small, random deviations from bilateral symmetry in structures that, typically, are bilaterally symmetrical. In plants, FA has been used as a tool for monitoring levels of ecological stress. In this work, I analyse the FA response to drought in the Holm oak (Quercus ilex) in SE Spain, to test whether FA increases or diminishes when climatic conditions are more stressful. Leaves from three different cohorts, corresponding to one drought year (1995) and two wet years (1996 and 1997) were collected at five sites contrasting in rainfall conditions, from very low to rather high rainfall. In two of the zones, two different morphs of leaves were collected. Furthermore, one of the sites was chosen close to a river, to examine the effect of water enhancement in the trees during drought and post-drought conditions. The results revealed no differences in response to drought in terms of FA between leaf morphs. However, while plants from rainy sites showed a decline in leaf FA from drought to wet years, the water-enhanced site and the dry sites showed scant or negligible differences between years. There was a significant decrease in FA from rainy sites to dry sites. These results suggest that (1) plants living in the more stressful sites are more symmetrical, (2) the more symmetrical plants respond less to yearly variations in drought stress, and (3) the response to yearly variations in drought depend on the climatic conditions in which a tree is living
Keywords: Drought; Fluctuating asymmetry; Holm oak; Mediterranean climate; Quercus ilex; RAINFALL

Stable hydrogen and oxygen isotope studies of rainfall and streamwaters for two contrasting holm oak areas of Catalonia, northeastern Spain - Neal, C; Neal, M; Warrington, Anita; Avila, a (Journal of Hydrology, 1992)
Results are presented of a study of stable hydrogen and oxygen isotopes in rainfall and streamwaters for the Montseny and Prades areas in northeastern Spain: results cover the full year of 1991. The isotopic pattern for rainfall is similar for both areas: there is a wide range in isotopic contents and the results show a strong, near-linear trend, 62H = 7.9 x 6~80 + 9.8 (N = 59; r 2 = 0.952), the 'local meteoric line'. There is slight curvature to the data which may be related to the sources of water vapour forming the rainfall. Within the streams, the isotopic variability is much less than that of the rainfall although the data lie on, or very near to, the meteoric line. Data for detailed collections during storm events show more scatter than those collected regularly on a fortnightly basis. The event data show a linear feature that conforms to the local meteoric line. These results indicate that: (1) the main supply of water to the stream stormflow comes from water stored in the catchment prior to the event; (2) waters of more than one isotopic composition reside within the catchment and are transferable to the stream during storm events; (3) the main process of water transfer from the catchment back to the atmosphere comes from transpiration by the trees and (possibly) complete evaporation from the near-surface soil horizons and the tree canopy; (4) the isotopic technique cannot be used for quantitative hydrograph separation in this instance at least two water types can be present within the catchment at any given time.
Keywords: isotope composition (voyant); RAINFALL; stream water